Validating the Balance of Semi-Professional Dancers by Use of the Jenaer-Standing-Stability-Score (JESS-Score) - Buder, Anja; Derlien, Steffen; Loudovici-Krug, Dana; Best, Norman (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2021)
Introduction Postural control plays a central role in dance performance. The most dance styles contain manifold balance requirements. However, the data available on balance performance in dance is meagre. The dancers’ balancing ability depends on different components, which are still not totally understood. It can be assumed that standing stability as well as balance and therefore the test results of dancers are better than those of the recently published norm values. The aim of the study is to compare and verify the published standard values of the Jenaer-Standing-Stability-Score (JESS-Score).Material and Methods 24 dancers were included and measured with the first version of the recently published JESS-Score. 11 items include the assessment of mobility, sensorimotor skills, posture control and strength endurance. The dancers average test results are compared to the norm population.Results The dancers reached the norm or were even better concerning the tested items of the JESS-Score.Conclusion Standing stability and balance are basic requirements for dancing. The components measured by the JESS-Score are clearly involved in the equilibrium performance. Moreover, it shows the applicability of the JESS-Score norm values to a healthy, but untrained control population.
Keywords: postural balance; dancing; scoring method; standing position